Willie Jonker se Teologiese Etiek - Van Niekerk, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The theological ethics of Willie Jonker The article deals with the South African Dutch Reformed theologian W.D. (Willie) Jonker’s (1929-2006) contribution to theological ethics. Three perspectives onhis ethics are developed, viz. foundational, methodological and substantive perspectives. The first relates to his idea that the foundation of ethics is the correlation between doctrine and life. Ethics is the outcome of the reconciliation in Christ as activated by the work of the Spirit, through which the totality of human life in the world is sanctified through the mediation of the life of the church. The second, methodological perspective deals with the relationship between ethics and hermeneutics. Here Jonker’s complex and original work on the grounding of ethical claims on Scripture is discussed, and much attention is paid to his appropriation of Calvin in this regard. The third, substantive perspective deals with an area where Jonker made a distinctly new contribution to theological ethics in Dutch Reformed orientated South Africa during apartheid, viz. the development of a social ethics. This aspect of his work was particularly inspirational for the development of a critical consciousness about apartheid in Dutch Reformed circles sionce the 1980’s. The article is concluded with a couple of critical and evaluative remarks.